Effect of coating thickness of iron oxide nanoparticles on their relaxivity in the MRI - Farzaneh Hajesmaeelzadeh; Saeed Shanehsazzadeh; Cordula Grüttner; Fariba Johari Daha; Mohammad Ali Oghabian (Iranian Journal of Basic Medical Sciences, 2016)
Objective(s):Iron oxide nanoparticles have found prevalent applications in various fields including drug delivery, cell separation and as contrast agents. Super paramagnetic iron oxide (SPIO) nanoparticles allow researchers and clinicians to enhance the tissue contrast of an area of interest by increasing the relaxation rate of water. In this study, we evaluate the dependency of hydrodynamic size of iron oxide nanoparticles coated with Polyethylene  glycol (PEG) on their relativities with 3 Tesla clinical MRI. Materials and Methods: We used three groups of nanoparticles with nominal sizes 20, 50 and 100 nm with a core size of 8.86 nm, 8.69 nm and 10.4 nm that they were covered with PEG 300 and 600 Da. A clinical magnetic resonance scanner determines the T1 and T2 relaxation times for various concentrations of PEG-coated nanoparticles. Results: The size measurement by photon correlation spectroscopy showed the hydrodynamic sizes of MNPs with nominal 20, 50 and 100 nm with 70, 82 and 116 nm for particles with PEG 600 coating and 74, 93 and 100 nm for  particles with PEG 300 coating, respectively. We foud that the relaxivity decreased with increasing overall particle size (via coating thickness). Magnetic resonance imaging showed that by increasing the size of the nanoparticles, r2/r1 increases linearly. Conclusion: According to the data obtained from this study it can be concluded that increments in coating thickness have more influence on relaxivities compared to the changes in core size of magnetic nanoparticles.